Advances in theoretical hydrology : a tribute to James Dooge - Dooge, James; O'Kane, J. P., 1943- (European Geophysical Society series on hydrological sciences, 1992)
This Festschrift containing sixteen invited essays and papers is a tribute to the distinguished Irish hydrologist James Dooge on the occasion of his 70th birthday. His former students, colleagues and friends in fourteen countries, have provided a varied selection on his favourite topics: flow in open channels and unsaturated soil, and also from his major interest of recent years, large scale hydrology and global change. The book has three sections. The first section on hydrological processes contains six papers. The second section on large scale hydrology has four papers. Six historical, reflective and philosophical essays on the past and future of the hydrological sciences form the third section of the book.